Предмет: Алгебра,
автор: МиланаКлещёва
Помогите разложить трёхчлен на множители:
а) k^2 + 2kp + p^2
б) 1 - 2z + z^2
в) 9x^2 + 24xy + 16y^2
г) 81k^2 - 54kp + 9p^2.
Ответы
Автор ответа:
0
а) ![k^{2}+2kp+p^{2}=(k+p)^{2}
k^{2}+2kp+p^{2}=(k+p)^{2}](https://tex.z-dn.net/?f=k%5E%7B2%7D%2B2kp%2Bp%5E%7B2%7D%3D%28k%2Bp%29%5E%7B2%7D%0A)
б)![1-2z+z^{2}=1^{2}-2z+z^{2}=(1-z)^{2} 1-2z+z^{2}=1^{2}-2z+z^{2}=(1-z)^{2}](https://tex.z-dn.net/?f=1-2z%2Bz%5E%7B2%7D%3D1%5E%7B2%7D-2z%2Bz%5E%7B2%7D%3D%281-z%29%5E%7B2%7D)
в)![9x^{2}+24xy+16y^{2}=(3x)^{2}+24xy+(4y)^{2}=(3x+4y)^{2} 9x^{2}+24xy+16y^{2}=(3x)^{2}+24xy+(4y)^{2}=(3x+4y)^{2}](https://tex.z-dn.net/?f=9x%5E%7B2%7D%2B24xy%2B16y%5E%7B2%7D%3D%283x%29%5E%7B2%7D%2B24xy%2B%284y%29%5E%7B2%7D%3D%283x%2B4y%29%5E%7B2%7D)
г)
б)
в)
г)
Автор ответа:
1
k² + 2kp + p² = (k + p)² = (k + p)(k + p)
1 - 2z + z² = (1 - z)² = (1 - z)(1 - z)
9x² + 24xy + 16y² = (3x + 4y)² = (3x + 4y)(3x + 4y)
81k² - 54kp + 9p² = (9k - 3p)² = (9k - 3p)(9k + 3p)
1 - 2z + z² = (1 - z)² = (1 - z)(1 - z)
9x² + 24xy + 16y² = (3x + 4y)² = (3x + 4y)(3x + 4y)
81k² - 54kp + 9p² = (9k - 3p)² = (9k - 3p)(9k + 3p)
Похожие вопросы
Предмет: Математика,
автор: alishkakasatkina
Предмет: Химия,
автор: kludmila045
Предмет: Українська мова,
автор: Аноним
Предмет: Алгебра,
автор: madinashaizaman
Предмет: Математика,
автор: тома52